The Effect of GeoGebra-Based Instruction on Students’ Conceptual Understanding of Exponential Functions - Amalia Rasikhah Earliand; Alfisyahra Alfisyahra; Muh Hasbi; Dasa Ismaimuza (Universitas Islam Lamongan, 2026)
Exponential functions pose conceptual challenges for secondary students due to their abstract nature. This quasi-experimental study investigated the effect of GeoGebra-based instruction on Grade 10 students’ conceptual understanding in two Indonesian senior high schools (N = 132). A validated four-item essay test (r > 0.219; Cronbach’s Alpha = 0.71) was administered before and after instruction. Mann–Whitney U analysis showed a significant difference in posttest conceptual understanding between the GeoGebra and conventional groups (p < .001), with a moderate-to-large effect size (r = 0.44). These results provide classroom-based empirical evidence that dynamic visualization through GeoGebra strengthens students’ conceptual understanding and supports its structured integration in conceptually demanding mathematics topics.